2021
DOI: 10.1111/mmi.14804
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid divergence in the ligand‐binding pocket of Vibrio LuxR/HapR proteins determines the efficacy of thiophenesulfonamide inhibitors

Abstract: Vibrio bacteria are pathogens of fish, shellfish, coral, and humans due to contaminated seafood consumption. Vibrio virulence factors are controlled by the cell-to-cell communication called quorum sensing, thus this signaling system is a promising target for therapeutic design. We screened a compound library and identified nine compounds, including several 2thiophenesulfonamides, that inhibit the master quorum sensing transcription factor LuxR in Vibrio campbellii but do not affect cell growth. We synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…38 Finally, while the thiophenesulfonyl chlorides A−C yield the most active compounds, benzenesulfonyl chloride (E) derivative 1E was reasonably active as well. 38 This is a much more inexpensive sulfonyl chloride, and a huge variety of arylsulfonyl chlorides are commercially available. A library based on benzenesulfonyl chloride derivatives would be a cost-effective way to scale this project up for a larger laboratory.…”
Section: ■ Library Designmentioning
confidence: 96%
See 4 more Smart Citations
“…38 Finally, while the thiophenesulfonyl chlorides A−C yield the most active compounds, benzenesulfonyl chloride (E) derivative 1E was reasonably active as well. 38 This is a much more inexpensive sulfonyl chloride, and a huge variety of arylsulfonyl chlorides are commercially available. A library based on benzenesulfonyl chloride derivatives would be a cost-effective way to scale this project up for a larger laboratory.…”
Section: ■ Library Designmentioning
confidence: 96%
“…From a compound library screen, several sulfonamide molecules were identified that inhibit LuxR function. 38 Interestingly, an analogous screen identified a sulfonamide called Qstatin that inhibits the LuxR homologue SmcR in Vibrio vulnificus (Figure 1). Thus, the Qstatin structure was identified as a starting point and positive control for subsequent studies.…”
Section: ■ Research Overviewmentioning
confidence: 99%
See 3 more Smart Citations